Pharmacological evaluation and preparation of nonsteroidal anti-inflammatory drugs containing an N-Acyl hydrazone subunit - Melo, Thais Regina Ferreira de [UNESP]; Chelucci, Rafael Consolin [UNESP]; Pires, Maria Elisa Lopes [UNESP]; Dutra, Luiz Antonio [UNESP]; Barbieri, Karina Pereira [UNESP]; Bosquesi, Priscila Longhin [UNESP]; Trossini, Gustavo Henrique Goulart; Chung, Man Chin [UNESP]; Santos, Jean Leandro dos [UNESP] (MDPI, 2014)
A series of anti-inflammatory derivatives containing an N-acyl hydrazone subunit (4a–e) were synthesized and characterized. Docking studies were performed that suggest that compounds 4a–e bind to cyclooxygenase (COX)-1 and COX-2 isoforms, but with higher affinity for COX-2. The compounds display similar anti-inflammatory activities in vivo, although compound 4c is the most effective compound for inhibiting rat paw edema, with a reduction in the extent of inflammation of 35.9% and 52.8% at 2 and 4 h, respectively. The anti-inflammatory activity of N-acyl hydrazone derivatives was inferior to their respective parent drugs, except for compound 4c after 5 h. Ulcerogenic studies revealed that compounds 4a–e are less gastrotoxic than the respective parent drug. Compounds 4b–e demonstrated mucosal damage comparable to celecoxib. The in vivo analgesic activities of the compounds are higher than the respective parent drug for compounds 4a–b and 4d–e. Compound 4a was more active than dipyrone in reducing acetic-acid-induced abdominal constrictions. Our results indicate that compounds 4a–e are anti-inflammatory and analgesic compounds with reduced gastrotoxicity compared to their respective parent non-steroidal anti-inflammatory drugs.
Keywords: Anti-inflammatory; Analgesic; Hydrazone; Molecular hybridization; Non-steroidal; Anti-inflammatory; NSAID; Docking; Molecular modeling; COX